Modernizing China. - Lam, W. Raphael; Rodlauer, Markus; Schipke, Alfre (INTERNATIONAL MONETARY FUND, 2017)
China is at a critical juncture in its economic transformation as it tries to rebalance what is generally seen as an exhausted growth model. A unifying theme across the reforms that will deliver this transformation is that it can no longer be achieved by raising the amount of physical investment and government direction of resource allocation. Instead China is building a new set of policy frameworks that will allow markets to function more effectively-not unfettered markets, but markets that work efficiently, in line with broad social and other policy goals, and in a sustainable way. Hence, China is now building a new soft infrastructure, that is, the institutional plumbing that underpins and guides the functioning of markets as the key organizing principle toward achieving sustained economic and social progress. Against this background, this volume provides policymakers, academics, and the public with valuable information about policies and institutions in China today. It also looks at the road ahead and key principles that can help China in navigating it. The book focuses on issues crucial in the country's transformation, such as tax policy and administration, social security, state-owned enterprise reform, medium-term expenditure frameworks, the role of local government finances, capital account liberalization, and renminbi internationalization. As China moves toward a more price-based allocation of resources, strengthening monetary policy frameworks and financial sector regulation will be particularly important in channeling resources to the most productive sectors and minimizing the risks of financial sector stress. Also, upgrading statistical frameworks will be critical for macroeconomic policymaking and investors.